Human Mesenchymal Stem Cells Provide Protection against Radiation-Induced Liver Injury by Antioxidative Process, Vasculature Protection, Hepatocyte Differentiation, and Trophic Effects. (28th November 2013) - Francois, Sabine; Mouiseddine, Moubarak; Allenet-Lepage, Bénédicte; Voswinkel, Jan; Douay, Luc; Benderitter, Marc; Chapel, Alain
Abstract : To evaluate the potential therapeutic effect of the infusion of hMSCs for the correction of liver injuries, we performed total body radiation exposure of NOD/SCID mice. After irradiation, mir-27b level decreases in liver, increasing the directional migration of hMSCs by upregulating SDF1 α . A significant increase in plasmatic transaminases levels, apoptosis process in the liver vascular system, and in oxidative stress were observed. hMSC injection induced a decrease in transaminases levels and oxidative stress, a disappearance of apoptotic cells, and an increase in Nrf2, SOD gene expression, which might reduce ROS production in the injured liver. Engrafted hMSCs expressed cytokeratin CK18 and CK19 and AFP genes indicating possible hepatocyte differentiation. The presence of hMSCs expressing VEGF and Ang-1 in the perivascular region, associated with an increased expression of VEGFr1, r2 in the liver, can confer a role of secreting cells to hMSCs in order to maintain the endothelial function. To explain the benefits to the liver of hMSC engraftment, we find that hMSCs secreted NGF, HGF, and anti-inflammatory molecules IL-10, IL1-RA contributing to prevention of apoptosis, increasing cell proliferation in the liver which might correct liver dysfunction. MSCs are potent candidates to repair and protect healthy tissues against radiation damages.